Multimedia Educational Tools As An Important Factor of The Development Of Students' Competence - pcadmin, Rasulova Zilola Durdimurotovna (Genius Journals, 2024)
This article talks about multimedia educational tools, and by applying them to the teaching processes of the higher education system, the content of the levels of formation of students' knowledge, skills and qualifications is highlighted.
Keywords: modern educational tools; multimedia concept; creative thinking